Vaccine Certificates Must Go Digital: An Urgent Call for Better Public Health Outcomes - Jarbas Barbosa da Silva Júnior; Sebastian Garcia-Saiso; Myrna Marti; Daniel Salas; Marcela Contreras; Martha Velandia-Gonzalez; Daniel Luna; Jennifer Nelson; James Fitzgerald; Ernesto Bascolo; Ivy Lorena Talavera Romero; May Chomali; et al. (JMIR Public Health and Surveillance)
AbstractFrom our roles within international public health organizations, we have collectively witnessed the global challenges presented by outdated health information systems, platforms, and applications. The COVID-19 pandemic has clearly exposed the limitations of our current paper-based vaccine certification methods and highlighted the deficiencies of outdated technological platforms that lack interoperability standards, a situation that underscores the critical need for a digital transformation in how we manage and verify immunization records. Digital vaccination certificates are understood to be secure, electronically stored, and easily accessible records that provide verifiable proof of a person’s immunization status. The Pan American Health Organization (PAHO) envisions leveraging digital technologies to strengthen health systems, enhance data-driven decision-making, and improve health outcomes. The organization’s vision emphasizes the integration of innovative technologies to build resilient and responsive health systems capable of addressing modern public health challenges. In an era of unprecedented technological advancement, our continued reliance on paper-based vaccine certificates is not just anachronistic—it is a significant liability for global public health that impacts the efficiency and effectiveness of our health systems on multiple fronts, limiting our ability to respond to public health crises effectively. With the strategic guidance from its Member States, PAHO has agreed to move toward the digital transformation of the health sector across the entire continent with an initiative that aims to improve health outcomes, ensure equitable access to health services, and enhance the overall efficiency of health systems in the Americas. The roadmap for this digital transformation outlines strategic actions and goals to achieve a connected, efficient, and resilient health sector.